Kinetic aspects on ferric arsenate formation in a fix bed gas-solid reaction system (2015)
The fixation of arsenic contained in gases produced during pyrometallurgical processes by using solid ferric oxide was studied in the range 873-1073 K under different oxygen potential and solid aggregates porosities. Arsenic fixation on solid iron oxides is described by the pore blocking model under the studied conditions. The solid product of the reaction has a molar volume 3 times larger than the solid reactant causing fast decreasing of the inter-granular spacing. The activation energies of arsenic fixation reaction are 34.96 and 35.46 kJ/mol for porosities of 0.88 and 0.74 respectively, and for porosity of 0.55 the activation energy was 26.88 kJ/mol. These values of activation energy show that intra-pellets diffusion has an effect only in samples with 0.55 porosity. Minor sintering of particles was detected. Industrial application of the concept demands a reaction system, which in is required better gas-solid contact for attaining larger conversions.